Associations Between Lean Mass, Muscle Strength and Power, and Skeletal Size, Density and Strength in Older Men. (12th June 2018) - Chalhoub, Didier; Boudreau, Robert; Greenspan, Susan; Newman, Anne B; Zmuda, Joseph; Frank‐Wilson, Andrew W; Nagaraj, Nayana; Hoffman, Andrew R; Lane, Nancy E; Stefanick, Marcia L; Barrett‐Connor, Elizabeth; Dam, Tien; et al.
ABSTRACT: Studies examining the relationship between muscle parameters and bone strength have not included multiple muscle measurements and/or both central and peripheral skeletal parameters. The purpose of this study was to explore the relationship between lean mass, muscle strength and power, and skeletal size, bone density, and bone strength. We studied the association between appendicular lean mass (ALM), grip strength, and leg power, and central quantitative computed tomography (QCT) parameters in 2857 men aged 65 years or older; peripheral QCT was available on a subset ( n  = 786). ALM, grip strength, and leg power were measured by dual‐energy X‐ray absorptiometry (DXA), Jamar dynamometer, and the Nottingham Power Rig, respectively. Multivariable models adjusting for potential confounders including age, race, study site, BMI, and muscle measurements were developed and least squares means were generated from linear regression models. For the multivariable model, percent differences of bone parameters between lowest (Q1) and highest quartiles (Q4) of ALM, grip strength, and leg power were reported. ALM was significantly associated with central and peripheral QCT parameters: percent higher values (Q4 versus Q1) ranging from 3.3% (cortical volumetric bone mineral density [vBMD] of the femoral neck) to 31% (vertebral strength index of the spine). Grip strength was only significantly associated with radial parameters: percent higher values (Q4 versus Q1) ranging from 2.5% (periosteal circumference) to 7.5% (33% axial strength index [SSIx]). Leg power was associated with vertebral strength and lower cross‐sectional area with percent lower values (Q4 versus Q1) of –11.9% and –2.7%, respectively. In older men, stronger associations were observed for ALM compared to muscle strength and power. Longitudinal studies are needed to examine the relationship between independent changes in muscle measurements and skeletal size, density and strength. © 2018 American Society for Bone and Mineral Research.